TRAVELSASSY Holdings / Fatin Rusydina Roshidi ... [et al.] - Roshidi, Fatin Rusydina; Ramli, Ayu Farhana Amalin; Samat@Mat Juri, Nur Syahirah; Mohd Rafi, Nur Asmaa'lizalisma (2021)
The name of our business is TRAVELSASSY HOLDINGS and the name of our product is άνεση TRAVEL BAG. άνεση are derived from Greek language and it means comfort. To give comfort for our customer are the main purpose of our product so that they can enjoy their long journey peacefully and calm. άνεση TRAVEL BAG company provide three items in one packaging include blanket, neck pillow and eye mask. Based on our observation, majority other company just provide two items in one packaging which is pillow with blanket and blanket with bag. We make some improvise by adding eye mask in the packaging. This is the first product that come out with three items on one packaging. We sell the product with RM70. It is reasonable and affordable price so that the customer was afforded to buy it. As we don‟t have a shop to sell our product, we choose two shop as our vendor. The first vendor is Tumi Shop located at Kuala Lumpur International Airport (KLIA2). The shop address is Gateway @ KLIA2, Lot L2-135, Jalan KLIA 2/1, Terminal KLIA, 64000, Sepang. The location was strategic because at the left shop there are Luggage Storage Shop and at the right there are shop that will open soon. It is located near Jaya Grocer. In front of the shop, there are Hometown Hainan Coffee. The second vendor is Daiso located at Setia City Mall. The address is Setia City Mall, 7, Persiaran Setia Dagang Bandar Setia Alam Seksyen U13, 40170 Shah Alam Selangor Darul Ehsan, Malaysia. We choose this vendor because of we see the vendor have a potential to grow up our product so that a lot of people will know it. The online shopping was provided to ease the customer get our product. The online shopping was provided to customer if they don‟t have enough time to go store. Besides that, it is because of we just only have two vendors which is Tumi Shop located at Kuala Lumpur International Airport 2 (KLIA2) and Daiso located at Setia City Mall. So, it will hard for customer to get our product. Without of online shopping, it will give trouble to customer and waste their time to go store. Other than that, online shopping was give benefits to customers from other state such as Pahang, Perak and Terengganu to get our product as we just have vendor at Selangor. The business plan was important to grow up our business and to achieve the vision, mission and objective of company. The objective of our company is to give comfort to the 12 travellers during their journey, to give the best services to attract the customers and fulfil customers satisfaction, provide the high-quality product at affordable price and helps reduce neck and shoulder pain of customers. The vision of this company is to be one of the best companies who produce a unique and useful travel bag in Malaysia and make a various travel accessory such as travel tools, toiletries bags and make up bags. While the mission of the company is increase profits every month and open our own booths at KLIA and mall within 5 years.